2016
DOI: 10.1371/journal.pone.0162429
|View full text |Cite
|
Sign up to set email alerts
|

CT Pulmonary Angiography at Reduced Radiation Exposure and Contrast Material Volume Using Iterative Model Reconstruction and iDose4 Technique in Comparison to FBP

Abstract: PurposeTo assess image quality of CT pulmonary angiography (CTPA) at reduced radiation exposure (RD-CTPA) and contrast medium (CM) volume using two different iterative reconstruction (IR) algorithms (iDose4 and iterative model reconstruction (IMR)) in comparison to filtered back projection (FBP).Materials and Methods52 patients (body weight < 100 kg, mean BMI: 23.9) with suspected pulmonary embolism (PE) underwent RD-CTPA (tube voltage: 80 kV; mean CTDIvol: 1.9 mGy) using 40 ml CM. Data were reconstructed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…As such, it is crucial to calculate an accurate organ-equivalent dose before obtaining an estimation of cancer risk. At the moment there is no research has been found that evaluated the organ dose and cancer risk meticulously in CTPA examination elsewhere (Laqmani et al, 2016(Laqmani et al, , 2014Sabel et al, 2016;Sauter et al, 2018). This study aims to evaluate the dose exposure and to estimate cancer risk attributes from CTPA examinations based on the size and habitus of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…As such, it is crucial to calculate an accurate organ-equivalent dose before obtaining an estimation of cancer risk. At the moment there is no research has been found that evaluated the organ dose and cancer risk meticulously in CTPA examination elsewhere (Laqmani et al, 2016(Laqmani et al, , 2014Sabel et al, 2016;Sauter et al, 2018). This study aims to evaluate the dose exposure and to estimate cancer risk attributes from CTPA examinations based on the size and habitus of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the CT-system is used 32 cm body phantom calculation for determining the CTDIvol contribute for this finding. For CTPA, several studies that focused on CT dose and its optimization techniques [2,[7][8][9]. Surprisingly, there is no known comprehensively studied describing SSDE in different size of the patient in CTPA examination.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies reported that detrimental effects of radiation exposure are higher in susceptible patient populations, especially young women and children [11] As such, it is crucial to calculate an accurate organequivalent dose before obtaining an estimation of cancer risk. So far, no research has been found that evaluated the organ dose and cancer risk in CTPA examination based on previous study elsewhere [2,8,9,12]. This study aims to investigate the usefulness and effect of SSDE and patient size in evaluating radiation dose in CTPA examination and to estimate the cancer risk for each scan and organ.…”
Section: Introductionmentioning
confidence: 99%
“…The CT attenuation measured in main pulmonary trunk and left lower segmental pulmonary artery was found to be significantly higher in Group A than that in Group B (414.3±149.4 HU and 416.4±139.3 vs. 259.6±69.7 and 256.0±75.0 HU, p<0.0001) with no significant difference in signal-to-noise ratio (SNR) and contrast-to-noise-ratio (CNR) between the two groups (p>0.05). Most of the studies tested lowering kVp value with 80 or 100 kVp on CTPA examinations while achieving diagnostic images with low radiation dose, [35][36][37][38][39][40] while Boos and colleagues in their study further lowered the kVp to 70 without affecting image quality. It is well known that lowering tube voltage is associated with increased image noise, but this can be compensated by iterative reconstruction, which is confirmed by Boos study.…”
mentioning
confidence: 99%
“…Of these reported double lowdose CTPA studies, most of them were performed in patients with normal BMI (mean value <25 kg/m 2 ). 30,35 In contrast, Boos and colleagues presented diagnostic quality images in large patients as well, although they did not include extremely obese patients. The limitations of previous studies including only normal sized patients or with missing data on BMI 43 have been overcome by Boos' study, with findings offering additional value to the current literature.…”
mentioning
confidence: 99%